Pengembangan Permainan Scrabble Kimia Sebagai Media Pembelajaran Materi Reaksi Reduksi dan Oksidasi Kelas X SMA atau MA - Agnes Basa Prolina Silaban; Bayharti Bayharti (Edukimia, 2021)
Scrabble chemistry game as a learning media is one of the alternative media in doing practice questions to strengthen students concepts in the reduction and oxidation reaction material. The purpose of this study was to develop a chemical scrabble game media as a learning medium on reduction and oxidation reaction material. Type of research is Research and Development (R and D) research with 4-D model, namely the stages of define, design, develop and disseminate. This research is limited to the develop stage by conducting a validity test. Data was collected using a validation questionnaire for UNP Chemistry lecturers and chemistry teachers at SMAN 12 Padang. The data analysis technique used the Aiken V formula. The results of the validity test were 0.84 with valid and it was concluded that the chemical scrabble game developed was valid.